Teach yourself visually MacBook - Hart-Davis, Guy (John Wiley & Sons, Inc., 2018)
Whether youre new to computers or transitioning from a PC, this graphics-heavy guide will show you everything you need to know to get the most out of your new laptop. --
Includes bibliographical references. - Print version record
Keywords: MacBook (Computer); MacBook (Ordinateur); COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference